2004
DOI: 10.1167/iovs.04-0273
|View full text |Cite
|
Sign up to set email alerts
|

Macular Pigment and Percentage of Body Fat

Abstract: A relative lack of MP is associated with adiposity in men, and may underlie the association between body fat and risk for AMD progression in males. Further, the processes governing accumulation and/or stabilization of lutein and zeaxanthin in fat tissue appear to differ for males and females.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
85
2
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(96 citation statements)
references
References 41 publications
6
85
2
3
Order By: Relevance
“…Consistent with most previous reports (r ¼ À 0.078 to À 0.307), 8,12 we found a significant and inverse relationship between BMI and MPOD (r ¼ À 0.387, P ¼ 0.002), which could be due to the competition between retina and adipose tissue for the absorption and uptake of carotenoids. 8,12 To the best of our knowledge, even though sunlight exposure is a known risk factor of AMD no study to date has reported an association between the UV index and the level of MPOD.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with most previous reports (r ¼ À 0.078 to À 0.307), 8,12 we found a significant and inverse relationship between BMI and MPOD (r ¼ À 0.387, P ¼ 0.002), which could be due to the competition between retina and adipose tissue for the absorption and uptake of carotenoids. 8,12 To the best of our knowledge, even though sunlight exposure is a known risk factor of AMD no study to date has reported an association between the UV index and the level of MPOD.…”
Section: Discussionsupporting
confidence: 92%
“…8,12 To the best of our knowledge, even though sunlight exposure is a known risk factor of AMD no study to date has reported an association between the UV index and the level of MPOD. 11,13 This study provides evidence to this association, with a finding of reduced MPOD in subjects with higher UV index (r ¼ À 0.341, P ¼ 0.007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…61 Interestingly, Viroonudomphol et al have demonstrated lower levels of HDL in overweight and obese subjects, consistent with the possibility that a relative lack of HDL may impair transport and/or retinal capture of the carotenoids. 92 Of note, Seddon and co-workers have demonstrated a significantly increased risk of AMD in association with obesity.…”
Section: Association Of Carotenoids With Plasma Lipoproteinsmentioning
confidence: 81%
“…Although few studies did not find any relationship, 15 others showed an inverse association. [16][17][18] BMI is used as an indicator of 'generalized' obesity and waist circumference (WC) or waistto-hip ratio (WHR) as a measure of 'abdominal' obesity in epidemiological surveys. 19 South Asians have greater predisposition to abdominal obesity and visceral fat, 20,21 which is attributed to the so-called 'Asian Indian phenotype' characterized by increased WC despite lower BMI.…”
Section: Introductionmentioning
confidence: 99%